Impact of BARI aam3 mango variety adoption on the growers’ livelihood: Impact of BARI aam3 adoption on mango growers’ livelihood - Jannat, ST; Afrad, MSI; Haque, ME; Hasan, SS; Ivy, N A (Bangladesh Journal of Agriculture, 2026)
BARI aam3 is one of the 18 mango varieties that Bangladesh Agricultural Research Institute (BARI) released. It gained popularity throughout the country mainly due to its delightful taste and flavor. The study assessed the impact of BARI aam3 adoption on the growers’ livelihood. The research was purposively conducted in Porsha Upazila under Naogaon district and Nachole Upazila under Chapainawabganj district based on the abundance of cultivation of BARI aam3. Data were collected from 111 growers selected following a proportionate random sampling technique. Descriptive statistics and paired t-test were used for data analysis. BARI aam3 growers’ access to livelihood capitals increased by 49.4-91.7%. Growers’ access to human, social, natural, physical, and financial capitals was increased by 87.5%, 91.7%, 50.7%, 49.4%, and 52.8% respectively, due to the adoption of BARI aam3. They experienced an improvement in their knowledge, access to information, employment generation, decision-making, clothing, health, attitude, social status, and respect. There was increased involvement in social activities. Increases were also noticed in their forestry/trees, safe drinking water use, leased cultivable land, use of electricity, electronic communication devices, livelihood assets, furniture, agricultural tools, and annual agricultural income after BARI aam3 cultivation. Its cultivation also significantly influenced their increase in participation in income-generating activities. Bangladesh J. Agri. 2025, 50(2): 158-172